2016
DOI: 10.1364/boe.7.004569
|View full text |Cite
|
Sign up to set email alerts
|

Label-free fast 3D coherent imaging reveals pancreatic islet micro-vascularization and dynamic blood flow

Abstract: In diabetes, pancreatic β-cells play a key role. These cells are clustered within structures called islets of Langerhans inside the pancreas and produce insulin, which is directly secreted into the blood stream. The dense vascularization of islets of Langerhans is critical for maintaining a proper regulation of blood glucose homeostasis and is known to be affected from the early stage of diabetes. The deep localization of these islets inside the pancreas in the abdominal cavity renders their in vivo visualizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Additionally, our group recently developed an en face matrix based approach of OCT, which allows to increase the penetration depth by a factor of two [172], and could be advantageous for in vivo experiments. Finally, we are now interested in the development of functional imaging in FF-OCT, in fresh tissues, or in living animals, either by measuring changes in the blood flow, similarly to what has been achieved in OCT [132,173], or by directly measuring changes in the tissue biomechanics, or cellular activity. We believe that diagnosis capabilities will further benefit from this research, since it might soon be possible not only to detect static structural changes in a tissue, but also to detect how it reacts to different stimuli, or different drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our group recently developed an en face matrix based approach of OCT, which allows to increase the penetration depth by a factor of two [172], and could be advantageous for in vivo experiments. Finally, we are now interested in the development of functional imaging in FF-OCT, in fresh tissues, or in living animals, either by measuring changes in the blood flow, similarly to what has been achieved in OCT [132,173], or by directly measuring changes in the tissue biomechanics, or cellular activity. We believe that diagnosis capabilities will further benefit from this research, since it might soon be possible not only to detect static structural changes in a tissue, but also to detect how it reacts to different stimuli, or different drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Since the RNFL is damaged in glaucoma-the second leading cause of blindness worldwide [132]-and since RNFL birefringence is connected to layer integrity [133,134], the polarization properties of the RNFL were investigated as potential diagnostic markers for glaucoma. PS-OCT based assessment of the RNFL's birefringent properties might be particularly interesting since it was shown that polarization changes in experimental glaucoma can be observed earlier than RNFL thickness changes [135].…”
Section: Ps-oct In the Eyementioning
confidence: 99%
“…Data and images from Ref. [30]. ponentially in time, or, in other words, linearly with the number of cells.…”
Section: Growth and Bucklingmentioning
confidence: 99%
“…Additionally, compared with dynamic OCT techniques [116,132], we take advantage of the higher spatial resolution to capture subcellular variations, which further enable the cells to be revealed. To our knowledge, the contrast revealed by D-FF-OCT is therefore quite unique.…”
Section: Dynamic Ff-octmentioning
confidence: 99%
“…Finally, we are now interested in the development of functional imaging in FF-OCT, in fresh tissues, or in living animals, either by measuring changes in the blood flow, similarly to what has been achieved in OCT [132,173], or by directly measuring changes in the tissue biomechanics, or cellular activity. We believe that diagnosis capabilities will further benefit from this research, since it might soon be possible not only to detect static structural changes in a tissue, but also to detect how it reacts to different stimuli, or different drugs.…”
Section: Cellsmentioning
confidence: 99%